Cristina THE CORRELATION BETWEEN OF TRAUMA SCORE USING INJURY SEVERITY SCORE AND THE MORTALITY PATIENTS WITH SEVERE BRAIN INJURY AT GAMBIRAN PUBLIC HOSPITAL OF KEDIRI - P, Cristina Dewi (Universitas Nusantara PGRI Kediri, 2017)
Background :The high mortality rate of patients with severe head injury cause the importance to know the wellness of the injury. It can give information about physiological funtion disorders and neurological deficit. One of the anatomic scoring system that easily to use and can be used to predict the wellness of patient’s survival, at once can give the full score especially in patients with multiple injury, it is called injury severity score. Objective :The purpose of this study was to find out the correlation between traumatic score using the injury severity score and the mortality of patients with severe brain injury in Gambiran Public Hospital Of Kediri . Method : This is analitic research with cross sectional design. The sum of the respondents are 15, and using accidental sampling. Result : The result of the study that measured use Spearman Rho Test, showed the correlation score is 0.747 and the p value is 0.001 (a<0.05). Conclussion and Suggestion : There was correlation between traumatic score using the injury severity score and the mortality of patients with severe brain injury in Gambiran Public Hospital Of Kediri. From the result showed that injuryseverity score can be used as a tools to predict the mortality of patients with severe brain injury. Keywords : Trauma score, Injury severity score, mortality, brain severe injury